Determining radius of influence of the face in EPB shield tunneling by finite difference method - Sharifzadeh, Mostafa; Gharehdash, S.; Barzegar, M.
For the purpose of understanding the three-dimensional behavior of face tunnel, a three-dimensional finite difference simulation model, which includes all relevant shield tunneling components and allows for the modeling of the step-by-step construction process of the tunnel advance. The soil-structure interaction in shield tunneling is investigated by numerical solution. The results of three-dimensional ground displacements and stress pattern around a tunnel face and at the ground surface are examined. Results obtained from these analyses indicate that the general threedimensional stress and displacement patterns around a tunnel heading are very different from that at the plane strain transverse section. The distance required for the ground displacement to reach the plane strain condition will depend on the amount of plasticity developed around the tunnel opening. Consequently, face is the most important zone for the design engineer in EPB tunneling.